Lampens Dieter, and Lizet Klaasen, eds. Harmony in Bright Colors. Memling’s God the Father with Singing and Music-Making Angels Restored. Bélgica: Brepols Publishers, 2021 [ISBN: 978-2-503-58028-9] - Galisteo Rivero, Aurora (Eikón / Imago, 2022)
Reseña de la obra de Lampens Dieter, and Lizet Klaasen, eds. Harmony in Bright Colors. Memling’s God the Father with Singing and Music-Making Angels Restored. Bélgica: Brepols Publishers, 2021 [ISBN: 978-2-503-58028-9]